Mechanisms of U87 astrocytoma cell uptake and trafficking of monomeric versus protofibril Alzheimer's disease amyloid-β proteins. - Yali Li; Deshu Cheng; Ran Cheng; Xinyu Zhu; Tao Wan; Jianmiao Liu; Rongying Zhang (PLoS ONE, 2014)
A significant hallmark of Alzheimer's disease is the formation of senile plaques in the brain due to the unbalanced levels of amyloid-beta (Aβ). However, although how Aβ is produced from amyloid precursor proteins is well understood, little is known regarding the clearance and metabolism of various Aβ aggregates from the brain. Similarly, little is known regarding how astrocytes internalize and degrade Aβ, although astrocytes are known to play an important role in plaque maintenance and Aβ clearance. The objective of this study is to investigate the cellular mechanisms that mediate the internalization of soluble monomeric versus oligomeric Aβ by astrocytes. We used a combination of laser confocal microscopy and genetic and pharmacological experiments to dissect the internalization of sAβ42 and oAβ42 and their postendocytic transport by U87 human brain astrocytoma cell line. Both Aβ42 species were internalized by U87 cells through fluid phase macropinocytosis, which required dynamin 2. Depleting LDL receptor-related protein 1 (LRP1) decreased sAβ42 uptake more significantly than that of oAβ42. We finally show that both Aβ42 species were rapidly transported to lysosomes through an endolytic pathway and subjected to proteolysis after internalization, which had no significant toxic effects to the U87 cells under relatively low concentrations. We propose that macropinocytic sAβ42 and oAβ42 uptake and their subsequent proteolytic degradation in astroglial cells is a significant mechanism underlying Aβ clearance from the extracellular milieu. Understanding the molecular events involved in astrocytic Aβ internalization may identify potential therapeutic targets for Alzheimer's disease.